Internationalization of Construction Service Corporations: Impact of Size and International Experience - Ahsen Maqsoom; Hassan Ashraf; Imran Arif; Muhammad Umer; Tahira Nazir; Muhammad Najam; Khurram Shafi (IEEE Access, 2020)
The international services literature lacks research investigating the association between corporate size and corporate international experience with the internationalization. Using an integrated theoretical approach, this paper examines the internationalization of construction service corporations (CSCs) with specific emphasis on four dimensions: motives, firm-specific competitive advantages, home country-specific competitive advantages and locational considerations. A quantitative approach was adopted through a postal questionnaire survey. Out of 126 CSCS, 84 usable responses were analyzed giving 66.7% response rate. A comparative analysis was conducted using Mann-Whitney U test between the corporations having different sizes and international experiences. The findings show that CSCs of varied sizes did not concur over several firm-specific competitive advantages and home country-specific competitive advantages, whereas CSCs of varied international experiences were in disagreement over some locational factors. Small CSCs need to form joint ventures or partnerships in order to overcome their limitations. The government support is direly needed to promote internationalization of CSCs especially the younger and smaller ones which stand more vulnerable due to lack of opportunities in their domestic markets. The study will be helpful to managers and regulatory bodies towards creating a balanced playing field to develop the internationalization process for their service corporations.